Asian trans-displinary karst conference : Proceedings of the International Conference Yogyakarta Indonesia 7-10 January 2011 - Haryono, Eko (Yogyakarta:Faculty of Geography GMU, 2011)
Koleksi Referensi (Tidak Dipinjamkan)